The economic returns to a second official language: English in Quebec and French in the Rest-of-Canada - Louis N. Christofides; Robert Swidinsky (Institute for the Study of Labor (IZA), 2008)
Canada is a country with two official languages, French and English. The need for both languages in Quebec and the Rest-of-Canada (ROC) generates a demand for bilingualism and investment in the acquisition of a second official language. Knowledge of an additional language may be associated with enhanced earnings because it may reflect what might generically be called 'ability' bias or because it may actually be useful at the workplace. Until now, available data did not indicate whether bilingualism was actually being used at work. However, the 2001 Census reports, for the first time, whether an individual is bilingual and the extent to which this skill is actually used at work. Conditioning on both knowledge and use allows us to measure the additional earnings which accrue to the use of a second language more cleanly. We find very substantial, statistically significant, rewards to second official language use in Quebec and much smaller, not statistically significant, effects in the ROC.
urn:nbn:de:101:1-2008062508
Keywords: J01; 300; Wages; language knowledge; language use; Mehrsprachigkeit; Bildungsertrag; Sprache; Lohn; Kanada